PENGARUH PARTISIPASI ANGGARAN TERHADAP BUDGETARY SLACK DENGAN PSYCHOLOGICAL CAPITAL SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Rumah Sakit di Kota Jayapura) - Yuni Nuryani; Syaikhul Falah (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study aims to analyze the effect of budgetary participation on budgetary slack with psychological capital as intervening variable. This research was conducted in 6 hospitals in Jayapura City. Data collection in this research is using questionnaire where the respondent in thisresearch is Staff of Finance/ Administration and Program. The sampling technique used in this research is the census sampling method. The number of samples taken as many as 31 respondents.This research uses Partial Least Square (PLS) analysis technique using SmartPLS 3.0 software. The results of this study indicate that budget participation has significant effect on psychological capital, while psychological capital has significant effect on budgetary slack, however budget participation has no significant effect on budgetary slack and psychological capital to mediate the influence of budgetary participation on budgetary slack.